2020
DOI: 10.19053/01217488.v11.n2.2020.11142
|View full text |Cite
|
Sign up to set email alerts
|

Optimización del proceso de transesterificación del aceite de palma usando la técnica basada en Ultrasonido

Abstract: Este artículo muestra los resultados en el proceso de transesterificación en aceite de palma alto oleico utilizando la técnica de sonicación –US- en combinación con catalizadores heterogéneos. El efecto se evaluó por separado de la asistencia de EE. UU. Y del catalizador (TiO2, CaO, MgCO3, Na2CO3 y K2CO3). Posteriormente, se evaluó el biodiesel obtenido usando la combinación de US y catalizadores y se lograron rendimientos óptimos al usar esta combinación, pero es Na2CO3 el que proporciona los mejores resultad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…However, it can be noted that the highest oil conversion (60%) was achieved with the use of the CaO/SiO 2 composite with aratio of CaO to SiO 2 of 1:1. Based on these results, it should be noted that the oil conversion achieved in this study relatively lower compared to those reported by others for the same oil [20] [21]. In this respect, it should be acknowledged that more study is required to optimize the performance of the CaO/SiO 2 composites, in recognition of the higher performance of this catalyst reported by other works [3][19], together with the existence of the limestone and rice husk as low-cost raw materials.…”
Section: Catalytic Activity Testcontrasting
confidence: 73%
“…However, it can be noted that the highest oil conversion (60%) was achieved with the use of the CaO/SiO 2 composite with aratio of CaO to SiO 2 of 1:1. Based on these results, it should be noted that the oil conversion achieved in this study relatively lower compared to those reported by others for the same oil [20] [21]. In this respect, it should be acknowledged that more study is required to optimize the performance of the CaO/SiO 2 composites, in recognition of the higher performance of this catalyst reported by other works [3][19], together with the existence of the limestone and rice husk as low-cost raw materials.…”
Section: Catalytic Activity Testcontrasting
confidence: 73%